Intelligentsia as the ‘Russian Soul’: Paradoxes and Problems of the Russian Occidentalism - Broda, Marian (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2014)
The concept of ‘soul’ has for ages been a widespread and central category in the Russian national tradition, one through which the Russians seek to express their way of feeling and of comprehending their own community, territory, sense of existence, place and mission in the world. Thus, Russia is often treated as the ‘soul of the world,’ whereas her central power – actual (real) or potential (expected) – as the ‘soul of Russia.’ One of the consequences of the transformation over the last few centuries, symbolised by the name of Peter I, has been the emergence and rise of the Russian intelligentsia, perceived there, and perceiving itself, as at once an intellectual, cultural, ethical, social, political, ideological, historiosophical, and even quasi-sacral formation. In many ideas of the representatives of the Russian educated class the motif of ‘Russia’s soul,’ capable of reviving, revitalising and of transforming the existing reality, is associated namely with the intelligentsia. It is possible to find in them – even in those programmatically antisystemic and radically occidental – a whole array of features, structures and content typical of the Russian mental-cultural system, together with ways of perceiving, conceptualizing and problematizing the world – such that is, paradoxically, shared with the ideologies and supporters of the existing social order.